The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1365-2265.1986.tb03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Oral Diphosphonate in Normal Subjects

Abstract: Absorption of the diphosphonate etidronate (HEDP) was measured in 20 volunteer subjects at two centres (Glasgow and Madison) using a new method based on simultaneous administration of HEDP and intravenous 99mTc-HEDP (Osteoscan). The mean absorption of HEDP in fasting subjects in Glasgow was 3.5% (range 1-8.9%) and in Madison 1.5% (0.7-2.8%) (P less than 0.035). In four subjects studies were repeated with good agreement between results (mean 3.9 cf. 3.5%). Six subjects had studies repeated when drug was ingeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…Using radiolabelled pamidronate it is estimated that, in rats, 2% of the oral dose is absorbed (Ciba-Geigy, data on file). Estimates of the absorption of another bisphosphonate (etidronate) range from 1 to 9% (Fogelman et al, 1986). The effect of oral bisphosphonates on calcium release from bone may however be assayed indirectly by estimating their effect on the urinary Ca2+/Cr ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Using radiolabelled pamidronate it is estimated that, in rats, 2% of the oral dose is absorbed (Ciba-Geigy, data on file). Estimates of the absorption of another bisphosphonate (etidronate) range from 1 to 9% (Fogelman et al, 1986). The effect of oral bisphosphonates on calcium release from bone may however be assayed indirectly by estimating their effect on the urinary Ca2+/Cr ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal absorption of etidronate has been shown to be approximately 3% in the fasting state. 26 The administration ofa single dose of 0.04 mmol of etidronate per body weight (kg) 30 minutes before breakfast to healthy subjects revealed that only 1.04% of the total dose was excreted within 24 hours.4 When 200 mg of etidronate is given, the total excretion in the urine may be at least 8 pmol for 24 hours. It is not clear whether the effect ofpreventing stone recurrence can be achieved under these conditions.…”
Section: Effect Of Etidronate On the Adhesion Of Calcium Oxalate Crysmentioning
confidence: 99%
“…Bisphosphonates are poorly absorbed from the gastrointestinal tract (25)(26). In the case of clodronate, absorption lies between 1-6% of the administered dose (27)(28).…”
Section: Mechanism Of Action Of Bisphosphonatesmentioning
confidence: 99%